Business in government, and government in business - Fabela, Armand V. (Philippine Journal of Public Administration, 1988)
The government has embarked on a two-pronged approach to justify the continued operation of the government corporate sector. The "government in business" aspect involves the identification and disposition of government corporate entities that should not be subject to government control. The other aspect which is "business in government' concerns the complementary task of improvement, both in operations and monitoring of government corporations that must be retained. However, a number of questions arise in the debate for clear-cut criteria which shall be used to operationalize the approach. Several related issues and questions are also left unresolved including a clear definition of what a government corporation should be.